Another Case of Multilevel Cervical Disconnection Syndrome Presenting as Neonatal Encephalopathy - Kaylan M. Brady; Jonathan A. Blau; Spencer J. Serras; Jeremy T. Neuman; Richard Sidlow (Case Reports in Neurological Medicine)
Multilevel cervical disconnection syndrome (MCDS) is a rare malformation of the cervical spine previously documented in two toddlers. We present a case of a newborn first thought to have hypoxic-ischemic encephalopathy who was subsequently diagnosed with MCDS. The possibility of in utero presentation of the syndrome in this patient and the categorization of this syndrome in the spectrum of basilar skull/upper cervical malformation syndromes is discussed.